Pulse amplitude and delay modulation for indoor optical wireless communications - Slaiman, I. (Institute of Electrical and Electronics Engineers Inc., 2014)
Pulse amplitude and delay modulation technique 'PADM' for power efficient indoor optical wireless communications is proposed in this paper. PADM symbol structure and other specifications were investigated and compared to existing power efficient modulation techniques like PPM, DPPM, DPIM and DH-PIM. Using mathematical model and simulation it was found that for the same size of input block PADM has better bandwidth efficiency by â¼20 than other techniques, also two times higher transmission rate can be achieved when using same slot duration for all techniques, however the power efficiency still lower and need to be improved. It was found that using input block size M=3 provides the highest bandwidth efficiency versus best power requirements and thus considered as best input block sizes for this technique. Â© 2014 IEEE.